Uniaxial die compaction of food powders - Yus Aniza, Yusof, Dr.; Andrew, C. Smith, Dr.; Brian, J. Briscoe, Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/